Implementation of MeCUE 2.0 Method in Evaluating MyTelkomsel User Experiencel - Dela Arum, Hestiana; Ibrahim, Ali (Sistemasi: Jurnal Sistem Informasi, 2024)
This research aims to evaluate the user experience of MyTelkomsel application using the Modular Evaluation of Key Components of User Experience (MeCUE) 2.0 method. The growth of telecommunications technology and increased smartphone usage highlights the importance of apps that efficiently meet user needs. Although MyTelkomsel offers a wide range of services, many users have reported difficulties using certain features and dissatisfaction with the service, as seen in reviews on platforms like the Play Store, indicating challenges with user experience. This research focuses on identifying where the app meets user needs and where improvements are necessary. The findings show that while the app performs well in terms of usability and usefulness (scoring 6.31 and 6.25, respectively), it scores lower in commitment (4.64) and intention to use (4.74). These results suggest that while the app is functionally effective, improvements are still needed to enhance user loyalty and engagement.